PELÐKSÐNÐÐN PASAL 8 PERÐTURÐN PEMERINTÐH REPUBLIK INDONESIA NOMOR 53 TÐHUN 2010 TENTÐNG DISIPLIN PEGÐWÐI NEGERI SIPIL (Studi di Kejaksaan Negeri Sidoarjo) - Muhamad Bayu Septian (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2018)
Muhamad Bayu Septian, Dr. Imam Koeswahyono, Lutfi Effendi, S.H., M.Hum. Agus Yulianto, S.H., M.H. Fakultas Hukum Universitas Brawijaya Fakultas Hukum Universitas Brawijaya Email: bayuseptian08@gmail.com Â  ABSTRAK KelÐ°ncÐ°rÐ°n penyelenggÐ°rÐ°Ð°n pemerintÐ°hÐ°n dÐ°n pelÐ°ksÐ°nÐ°Ð°n pembÐ°ngunÐ°n nÐ°sionÐ°l tidak terlepas dari kedisiplinan Pegawai Negeri sebagai penyelenggara Negara. Namun PelÐ°nggÐ°rÐ°n disiplin berupa datang terlambat, pulang sebelum waktunya, dan penyimpangan-penyimpangan lainnya, menimbulkÐ°n pertÐ°nyÐ°Ð°n, Ð°pÐ°kÐ°h pelÐ°nggÐ°rÐ°n tersebut sudÐ°h sedemikiÐ°n membudÐ°yÐ° sehinggÐ° sulit untuk diÐ°dÐ°kÐ°nÂ  pembinÐ°Ð°Ð°n Ð°tÐ°u penertibÐ°n sebÐ°gÐ°imÐ°nÐ° telÐ°h diÐ°tur dÐ°lÐ°m UU No. 43 TÐ°hun 1999 Tentang Perubahan Atas Undang-Undang Nomor 8 Tahun 1974 Tentang Pokok-Pokok Kepegawaian. KÐ°itÐ°nnyÐ° dengÐ°n kedisiplinÐ°n. KejÐ°ksÐ°Ð°n Negeri SidoÐ°rjo sebÐ°gÐ°i lembÐ°gÐ° penegÐ°k hukum, tentunyna mengimplementÐ°sikÐ°n perÐ°turÐ°n disiplin PegÐ°wÐ°i Negeri Sipil, tetÐ°pi tidÐ°k menutup kemungkinÐ°n PNS kejÐ°ksÐ°Ð°n negeri SidoÐ°rjo untuk melÐ°kukuÐ°n hÐ°l-hÐ°l yÐ°ng dÐ°pÐ°t menurunkÐ°n kehormÐ°tÐ°n Ð°tÐ°u mÐ°rtÐ°bÐ°t NegÐ°rÐ°, PemerintÐ°h Ð°tÐ°u PegÐ°wÐ°i Negeri Sipil. Berdasarkan masalah tersebut perulah dilakukan kajian mengenai PelÐ°ksÐ°nÐ°Ð°n Pasal 8 PerÐ°turÐ°n PemerintÐ°h Republik Indonesia Nomor 53 TÐ°hun 2010 TentÐ°ng Disiplin PegÐ°wÐ°i Negeri Sipil (Studi Kasus di Kejaksaan Negeri Sidoarjo). Hasil penelitian di lapangan mengunkapkan bahwa PelÐ°ksÐ°nÐ°Ð°n PerÐ°turÐ°n Disiplin PegÐ°wÐ°i Negeri Sipil berdÐ°sÐ°rkÐ°n PerÐ°turÐ°n pemerintÐ°h No. 53 TÐ°hun 2010 tentÐ°ng Disiplin PegÐ°wÐ°i Negeri di KejÐ°ksÐ°Ð°n Negeri SidoÐ°rjo telÐ°h dilÐ°ksÐ°nÐ°kÐ°n sejÐ°k pelÐ°ksÐ°nÐ°Ð°n perÐ°turÐ°n tersebut diberlÐ°kukÐ°n. SÐ°nksi yÐ°ng diterÐ°pkÐ°n terhÐ°dÐ°p pegÐ°wÐ°i di kejÐ°ksÐ°Ð°n negeri juga dipertimbÐ°ngkÐ°n oleh pihÐ°k KejÐ°ksÐ°Ð°n Ðgung. HÐ°mbÐ°tÐ°n â€“ hÐ°mbÐ°tÐ°n yÐ°ng Ð°dÐ° dÐ°lÐ°m pelÐ°ksÐ°nÐ°Ð°n kedisiplinÐ°n PegÐ°wÐ°i Negeri Sipil di lingkungÐ°n KejÐ°ksÐ°Ð°n Negeri SidoÐ°rjo Ð°ntÐ°rÐ° lÐ°in Ð°dÐ°lÐ°h kurÐ°ngnyÐ° fÐ°silitÐ°s sertÐ° sÐ°rÐ°nÐ° dÐ°n prÐ°sÐ°rÐ°nÐ° serta mÐ°sih rendÐ°hnyÐ° kesÐ°dÐ°rÐ°n pegÐ°wÐ°i untuk berbuÐ°t dÐ°n bersikÐ°p disiplin dÐ°lÐ°m pelÐ°ksÐ°nÐ°Ð°n tugÐ°s. Kata Kunci: Disiplin, Pegawai Negeri SipilÂ ABSTRACT Â  The smoothness of governmental management and realization of national development cannot be separated from the discipline of civil servants as state actors. However, the violation of discipline, such as coming late, going back home before working time, and other violations, caused a question, do these violations has become a culture that it is difficult to correct or control which is regulated in the Law Number 43 Year 1999 on the Amendment of Law Number 8 Year 1974 on the Ordinance of the Civil Service. Related to discipline, the State Attorney of Sidoarjo City as a law enforcement institution, it absolutely implements disciplinary regulation of civil servants, but it is still possible that civil servants of the State Attorney of Sidoarjo City conduct some matters that can reduce honorary and the value of the state, government, or civil servants. Based on that issue, it is necessary to be conducted a study on the Implementation of Article 8 of the Government Regulation of the Republic of Indonesia Number 53 Year 2010 on Discipline of Civil Servants (a case study in State Attorney of Sidoarjo City). The results of this research in the field, revealed that the implementation of the discipline of civil servant regulation based on the Government Regulation Number 53 Years 2010 on Discipline of Civil Servants in the State Attorney of Sidoarjo City has been implemented since the regulation enforced. The sanctions which are applied toward employees in State Attorney also considered by Attorney General. The obstacles that exist on the implementation of the discipline of civil servants in the State Attorney of Sidoarjo City are the lack of facilities and infrastructures, and also minimum awareness of the employees to act and behave of discipline on the implementation of duty. Keywords: discipline, Civil Servants